Potensi Kandungan Senyawa Mahkota Bunga Mawar (Rosa damascena) - Chandra, Angeline; Damayanti, Putu Ayu Asri (Riviera Publishing, 2026)
Rosa damascena flowers are one of the rose species with abundant phytochemical content and have been extensively studied for their potential biological and pharmacological activities. Rosa damascena petals contain both volatile and non-volatile components. The main volatile compounds include ?-citronellol, geraniol, nerol, and phenylethyl alcohol (PEA), which play important roles in providing antispasmodic, vasorelaxant, anti-inflammatory, analgesic, and antidepressant effects. The non-volatile constituents consist of flavonoids and phenolics, which possess strong antioxidant activity. The organic acids and fatty acids contained in Rosa damascena petal extract also provide antimicrobial, anti-inflammatory, cardioprotective, and tissue regeneration effects. The vitamin content in this extract also strengthens antioxidant activity, maintains skin health, and accelerates wound healing. In vitro, in vivo, and clinical studies on Rosa damascena petal extract show broad pharmacological effects, ranging from antioxidant, anti-inflammatory, antimicrobial, antidiabetic, analgesic, sedative, neuroprotective, anticancer, and regenerative. The combination of bioactive compounds contained in Rosa damascena petals demonstrates the high potential of Rosa damascena in the development of pharmacology, cosmetics, and phytochemical-based therapies.